RATIONALIZATION OF THE PUBLISHING ENVIRONMENT OF ENGINEERING SCIENCES - S. M. Moroz (Moscow Polytechnic University, 2018)
The paper highlights the state and problems of the publishing environment related to technical sciences. The author analyzes the effectiveness of the application of impact factor and auxiliary bibliometric indicators to periodicals on technical sciences and comes to a conclusion that these indicators are not capable of resisting the attempts of manipulation and are often useless in revealing shady publishing practices and unscrupulous scientific journals. The paper substantiates the necessity of additional institutional measures of state regulation for the improvement of the publishing environment of technical sciences for increasing the productivity of researchers' activity. Among these measures the author proposes the additional criteria for inclusion scientific and technical periodicals into Higher Attestation Commission journal index (e.g. such index as the demand for a certain periodical), financial and reputational support of sectoral journals, organization of international scientific and technical sectoral journals under the support of joint ventures and international associations. These and other measures will facilitate the recovery of the publishing practices of applied and technical sciences through governmental regulation.